Cerebral Ischemic Events: An Overlooked Complication of Transthyretin Cardiac Amyloidosis in Afro-Caribbean Patients - Banydeen, Rishika; Signate, Aissatou; Tran, Tuan-Huy; Monfort, Astrid; Neviere, Remi; Inamo, Jocelyn (Frontiers in Neurology, 2022)
Aim The link between transthyretin cardiac amyloidosis (CATTR), and cerebral ischemic events (CIE) has only been hinted at till now, impeding progress in patient management. We seek to evaluate the frequency and characteristics of CIE in Afro-Caribbean patients followed for CATTR at our institution. Methods In this single-center retrospective observational study, Afro-Caribbean patients followed for CATTR between July 2005 and October 2019 were included. Occurrence of CIE was investigated, and their cardioembolic origin determined. Analysis of patient characteristics was conducted according to CIE and CATTR profiles. Results Overall, 120 CATTR patients were included: 17 wild-type ATTR (14.2%), 73 ATTR-V122I (60.8%), and 22 ATTR-I107V (18.3%). Thirty-six patients (30.0%) presented with CIE, including three transient ischemic attacks and 33 permanent ischemic strokes (75.8% with a cardioembolic pattern). CIE was concomitant with CATTR diagnosis in 16 (16/36: 44.4%) patients, while 14 patients (14/36: 38.9 %) experienced CIE over a median CATTR follow-up of 2.0 years (min-max range: 0.8–4.4 years). CATTR-CIE patients presented with atrial fibrillation (66.7%), left atrial enlargement (77.8%), a CHA2DS2-VASc ≥ 3 (97.2%) and a high anticoagulant intake (75.0%). Multivariate analysis retained only a high CHA2DS2-VASc score as an independent predictor of CIE risk (Hazard Ratio [95% CI]: 12.03 [1.62–89.24]). Conclusion Concomitant CIE, and CATTR diagnosis, potentially carries a worse prognosis. A CHA2DS2-VASc score ≥3 seems to be a strong and independent predictive factor of CIE in CATTR patients. Further studies are needed to assess the efficacy and timeliness of anticoagulation in CATTR patients, independently of atrial fibrillation.